Fractional Response Models - A Replication Exercise of Papke and Wooldridge (1996) - Harald Oberhofer; Michael Pfaffermayr (University of Innsbruck, Department of Public Finance, 2009)
This paper replicates the estimates of a fractional response model for share data reported in the seminal paper of Leslie E. Papke and Jeffrey M. Wooldridge published in the Journal of Applied Econometrics 11(6), 1996, pp.619-632. We have been able to replicate all reported estimation results concerning the determinants of employee participation rates in 401(k) pension plans using standard routines provided in Stata. As an alternative, we estimate a two-part model that is able to cope with the excessive number of boundary values of one in the data. The estimated marginal effects are similar to that derived in that paper. A small scale Monte Carlo simulation exercise suggests that the RESET tests proposed by Papke and Wooldridge in their robust form are useful for detecting neglected non-linearities in small samples.
Keywords: C15; C21; 330; Replication Exercise; Fractional Response Models; Two-Part Models; Monte Carlo Simulation.; Monte-Carlo-Methode; Modellierung; Simulation